Bentuk Penyajian Gendang Beleq Guntur Tlu Desa Songak Kecamatan Sakra Lombok Timur NTB - Rohin, Wiwin Familia (Universitas Hamzanwadi, 2019)
This study aims to describe the form of serving Gendang Beleq Guntur Tlu Songak village, Sakra Lotim district, NTB. The approach used in this research is descriptive qualitative. The object in this study is Gendang Beleq Guntur Tluwhich includes the performance. The subjects in this study were supporters of Gendang Beleq Guntur Tlu itself. The study focused on the form of gendang beleq gutur tlu. Data collection by observation, interviews and documentation. Data is done bydata reduction, data presentation, conclusion. To check the validity of the data, the data validity technique is used by triangulation technique. From the results of the study, it has been found about: (1) The form of the presentation Gendang Beleq Guntur Tlu is a form of dance orchestra music using various traditional musical instruments and covers Gendang Beleq Guntur Tlu itself, performance, performance procedures, floor pattern, dance, place of show, cosmetology, fashion, and music; (2) musical instruments used by gendang beleq, petuk, cemprang / ceng-ceng, reong, gong, oncer.